PREVALENCE OF INTESTINAL PARASITES IN A CHILD EDUCATION CENTER IN SOUTHEAST BRAZIL: PREVALENCE OF INTESTINAL PARASITES IN A CHILD EDUCATION CENTER IN SOUTHEAST BRAZIL - Almeida, Clarissa Pereira; Souza, Marco Antônio Andrade de (Brazilian Journal of Production Engineering, 2020)
Parasitic infections represent an important public health problem as they have a high prevalence in the population. Among the most prominent are the enteroparasitosis, which can affect nutritional balance, reduce food intake and interfere with nutrient absorption. In addition, they can cause significant damage to the host's intestines. The frequency of parasitic diseases varies according to the region, basic sanitation conditions and socioeconomic level. The present study aimed to evaluate the prevalence of enteroparasitosis in children and employees of a Child Education Center, administered by a non-governmental organization, in a municipality in the Southeast region of Brazil. Parasitological stool examinations were performed using the spontaneous sedimentation technique, in 106 individuals. Of the total number of individuals analyzed, 34 (32.07%) were positive for intestinal parasites. The most frequent protozoa were Entamoeba coli (17.92%) and Endolimax nana (9.43%) and among the helminths, Trichuris trichiura, Hookworm and Hymenolepis nana stood out, all with a prevalence of 1.89%. The occurrence of intestinal parasites and commensal in the analyzed population increase the need for educational, prophylactic actions and the correct treatment of parasitized individuals, thus guaranteeing a better health quality for the population.
Keywords: Parasitosis; Epidemiology; Children; Health